Pengaruh Dana Desa dan Faktor Ekonomi Lainnya terhadap Ketimpangan Pendapatan di Perdesaan Indonesia Tahun 2015-2022 - Salsabila, Sausan; Arcana, I Made (Seminar Nasional Official Statistics, 2024)
Income inequality in Indonesia in 2009-2015 fluctuated and tended to increase, especially in rural areas. Therefore, since 2015 the government has allocated village funds as an strategic effort to overcome income inequality in rural areas. Although there has been a decrease in income inequality in rural areas, the downward trend is relatively small and tends to stagnate every year. This study aims to obtain an overview of income inequality in rural areas and analyze the influence of village fund distribution supported by other economic factors on income inequality by applying panel data regression in the period 2015-2022 with a provincies analysis unit. The research results showed that village funds per capita and average number of years of schooling in rural areas have a significant negative effect on income inequality in rural areas, while the effect of poverty levels and per capita expenditure of the population in rural area is positive and significant. The government is expected to design more effective programs, such as targeted subsidies, to support income equality.